THE IMPACT OF CAPITAL ADEQUACY, LIQUIDITY AND OPERATIONAL RATIO ON BANKING FINANCIAL PERFORMANCE IN INDONESIA DURING THE COVID-19 PANDEMIC (2019-2021) - Muhammad Fadila Laitupa; Restia Christianty; Widya (SEAN Institute, 2023)
This study aims to determine the effect of Capital Adequacy, Liquidity, and Operations on the Financial Performance of Banking Listed on the Indonesia Stock Exchange (IDX) during the Covid-19 Pandemic. With the research time period, namely in 2019-2021. The ratios used in this study are the Capital Adequacy Ratio (CAR), Financing to Deposit Ratio (FDR), Operating Expenses on Operating Income (BOPO), and Return On Assets (ROA). This research is a quantitative research with secondary data types derived from annual reports of banking companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2021 period. The method used to collect samples is purposive sampling method. Based on predetermined criteria, there are 46 banks out of 47 commercial banks that meet the criteria. This study uses multiple linear regression analysis techniques. And the data is processed using the SPSS version 23 program. The results of this study indicate that capital adequacy (CAR), liquidity (FDR) and operations (BOPO) have an effect on financial performance (ROA), with a significance value of less than 0.05, namely the adequacy value capital (CAR) of 0.000, liquidity value (FDR) of 0.003 and operating value (BOPO) of 0.010.